Exploration of factors that motivate purchasing behaviour of green products by the millennial generation - Setshedi, Kentse (The IIE, 2019)
Environmental protection has increasingly become an important topic as society has become conscious of social issues in the last few decades. Social challenges such as air pollution and deforestation have become a great concern. Businesses have taken advantage of these challenges by manufacturing and retailing green products/ environmentally friendly products. Consumers have shown interest in purchasing these products. One of the consumer groups, namely millennials, are considered to be the part of those who purchase green products, and are regarded as the most powerful in terms of spending power and the ability to influence other consumers’ purchase behaviour. There is limited information on the South African millennials on factors that influence them to purchase green products. As a result, this research seeks to explore the factors that motivate South African millennials based in Gauteng Province to purchase green products.A qualitative research method was utilized in which data was collected through one-on-one semi-structured interviews. This research method allowed participants to comprehensively express themselves. The study found that price, convenience and visibility play a critical role in influencing the purchase of green products. These finding can assist marketers and brand managers in creating communication strategies that effectively target millennials.
Keywords: Consumer behaviour; Buying behaviour; Sustainability; Millennials; Green products; Sustainable living